Sexual transmission of American trypanosomiasis in humans: a new potential pandemic route for Chagas parasites - Araujo, Perla F; Almeida, Adriana B; Pimentel, Carlos F; Silva, Adriano R; Sousa, Alessandro; Valente, Sebastião A; Valente, Vera C; Britto, Manuela M; Rosa, Ana C; Alves, Rozeneide M; Hagström, Luciana; Teixeira, Antonio RL (Memórias do Instituto Oswaldo Cruz, 2017)
The Trypanosoma cruzi infection endemic in Latin America has now spread to several countries across four continents; this endemic involves triatomine vector-free protists. We hypothesised that the sexual transmission of T. cruzi contributes to the ongoing spread of Chagas disease. A short-term longitudinal study was conducted to evaluate this hypothesis. The study population comprised 109 subjects from four families, among whom 21 had been diagnosed with acute Chagas disease by direct parasitological analysis. Blood mononuclear cells and serum samples were obtained from each study subject once per year for three consecutive years. Enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence serological examinations were used to detect specific T. cruzi antibodies. Polymerase chain reaction of T. cruzi DNA revealed 188-nucleotide bands, which hybridised to a specific radiolabelled probe and were confirmed by cloning and sequencing. Three independent assessments at different time points revealed T. cruzi nuclear DNA footprints in 76% (83/109) of the study population with active infection. In contrast, the ELISA and indirect immunofluorescence assays detected the T. cruzi antibody in 28.4% (31/109) of the study samples. Moreover, the semen from 82.6% (19/23) of subjects people revealed harboured the 188- bp base pair T. cruzi footprint. Interestingly, the ejaculates of nuclear DNA-positive Chagas patient transmitted the T. cruzi upon peritoneal injection or infusion in the vagina of mice, and amastigotes were detected in the skeletal muscle, myocardium, vas deferens, and uterine tube. T. cruzi infections can be transmitted from females or males to naïve mates through intercourse, and progeny showed discrepancies between the ratios of nuclear DNA footprints and specific antibody that can be explained by the tolerance attained during early embryo growth. Additional studies are needed to develop drugs to eradicate the infections. Additionally, the importance of a vigorous education, information, and communication program to prevent sexually transmitted Chagas disease in humans cannot be underemphasised.